Attention Deficit Hyperactivity Disorder and Functional Defecation Disorders in Children. Issue 2 (February 2018) - Kuizenga-Wessel, Sophie; Koppen, Ilan J.N.; Vriesman, Mana H.; Di Lorenzo, Carlo; van Dijk, Marieke; Beelen, Maureen L.R.; Groeneweg, Michael; Stoffelsen, Reino J.; Benninga, Marc A.
ABSTRACT: Objectives: The aim of the study was to assess the prevalence of attention deficit hyperactivity disorder (ADHD) in children presenting with functional defecation disorders (FDDs) and to assess the prevalence of FDDs in children with ADHD. Methods: A cross-sectional cohort study was carried out between September 2014 and May 2016. Group 1: Parents of children with FDDs according to the Rome III criteria completed the Child Behavior Checklist and the VvGK (Dutch questionnaire based on the American Disruptive Behavior Disorder rating scale). Patients with ADHD subarea scores ≥70 on the Child Behavior Checklist and/or ≥16 on the VvGK were referred for further psychiatric evaluation. Group 2: Parents of children treated for ADHD at a specialized ADHD outpatient clinic completed a standardized questionnaire regarding their child's defecation pattern. Results: In group 1 (282 children with FDDs), 10.3% (7.1%–13.5% bias-corrected and accelerate confidence interval) were diagnosed with ADHD. Group 2 consisted of 198 children with ADHD, 22.7% (17.6–28.8 bias-corrected and accelerate confidence interval) fulfilled the Rome III criteria for an FDD. Children with both an FDD and ADHD reported urinary incontinence significantly more often compared to children with an FDD or ADHD alone: 57.1% in FDD + ADHD versus 22.8% in FDD alone ( P  < 0.001) and 31.1% in ADHD + FDD versus 7.8% in ADHD alone ( P  < 0.001). Conclusions: Approximately 10.3% of children with FDDs had ADHD and 22.7% of children with a known diagnosis of ADHD fulfilled the Rome III criteria for an FDD. This observation suggests that screening for behavioral disorders and FDDs should be incorporated into the diagnostic workup of these groups of children.